2020
DOI: 10.4018/978-1-7998-2426-8.ch001
|View full text |Cite
|
Sign up to set email alerts
|

The Embodied Impact of Existing Building Stock

Abstract: This chapter provides the reader with a better understanding of the life cycle environmental impacts, with a focus on the embodied impact of existing building stock. A systematic literature review is conducted to paint a clear picture of the current research activities and findings. The major components of embodied impact and parameters influencing the embodied impact are outlined and explained. Lastly, this chapter discusses the major barriers for the embodied impact assessment, and a potential analysis frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Figure 1 illustrates the embodied carbon through the building life-cycle, including upstream and downstream emission. high number of variables [3,4], including building materials [5] and building construction types [2]: there is inadequate published information on whole building life-cycle embodied energy reports [6].…”
Section: Embodied Carbonmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 illustrates the embodied carbon through the building life-cycle, including upstream and downstream emission. high number of variables [3,4], including building materials [5] and building construction types [2]: there is inadequate published information on whole building life-cycle embodied energy reports [6].…”
Section: Embodied Carbonmentioning
confidence: 99%
“…Regardless, the commonly accepted guidelines and methods of assessment and measurement for embodied energy have not been established. Previous studies demonstrate considerable variation in reported embodied energy values due to the high number of variables [3,4], including building materials [5] and building construction types [2]: there is inadequate published information on whole building life-cycle embodied energy reports [6]. Aside from a lack of consensus on measurement and procedures, embodied energy emissions and related carbon emissions are being largely ignored [7] as the focus is solely on operating energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualized social appraisal affordance positively influences cognitive exercise engagement. The actualized social appraisal affordance helps users build a more affective social connection and friendly social comparison environment by identifying people with similar exercise backgrounds or interests and staying connected with them [22,23]. These social connection and comparison environments are helpful for users to develop positive feelings about performing fitness activities.…”
Section: Actualized Social Appraisal Affordance and Exercise Engagementmentioning
confidence: 99%
“…These social connection and comparison environments are helpful for users to develop positive feelings about performing fitness activities. Because people are more likely to receive favorable comments when their fitness performance looks good and receive encouragement and help from their friends within this social connection if their fitness performance looks not good [22,23]. Hence, we hypothesize:…”
Section: Actualized Social Appraisal Affordance and Exercise Engagementmentioning
confidence: 99%